Cost Analysis of Inpatient Heart Failure Treatment in Jogja Hospital Based On INA-CBG's Tariffs In 2023 - Ingenida Hadning; Ahadijatul Kubra (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2025)
Heart failure is a catastrophic disease that requires long-term care, resulting in high costs. This study is the first to evaluate the INA-CBG's tariff based on the Minister of Health Regulation Number 3 of 2023 for treating inpatient heart failure. This study aims to determine the difference in the actual costs of inpatient heart failure treatment in Jogja Hospital with INA-CBG's tariff based on Permenkes Number 3 of 2023. This study is an observational study with a cross-sectional research design and retrospective data collection of medical record data and patient cost data in 2023. Data were analyzed using descriptive analysis methods and a one-sample t-test. Data were obtained from 104 patients. The results of this study found that the average real cost for the treatment of inpatient heart failure with code I-4-12-I class 1 is IDR10.302.093 ± Rp5.749.499, class 2 is IDR IDR4.184.959 ± Rp681.730, and class 3 is IDR5.123.572 ± Rp2.242.239. The average real cost for the treatment of inpatient heart failure with code I-4-12-II class 1 is IDR9.764.750 ± Rp5.208.499; class 2 is IDR6.734.834 ± Rp3.82.345, and class 3 is IDR8.549.362 ± Rp4.288.906. The average real cost for treating inpatient heart failure with code I-4-12-III class 1 is IDR6.073.828; class 2 is IDR16.885.496, and class 3 is IDR14.326.130±Rp7.565.598. The average real cost was higher than the INA-CBG's tariff, with a significant difference, so the hospital suffered a loss.